A High Efficiency Low-Voltage Soft Switching DC–DC Converter for Portable Applications - P. Amiri; M. Sharafi (Journal of Electrical and Computer Engineering Innovations, 2013)
This paper presents a novel control method to improve the efficiency of low-voltage DC-DC converters at light loads. Pulse Width Modulation (PWM) converters have poor efficiencies at light loads, while pulse frequency modulation (PFM) control is more efficient for the same cases. Switching losses constitute a major portion of the total power loss at light loads. To decrease the switching losses and to increase efficiency, converters based on soft-switching are utilized. This paper presents the design of a soft-switching DC-DC buck converter in a 90-nm CMOS technology. Simulation results by HSPICE shows a 21 mV output ripple on a 0.5 V output voltage for an input voltage of 1.4 V. Finally, the efficiency of 95% at a load current of 50 mA having 74 mA of current ripple is achievable.